An exploration of the relationship between consociationalism and stability in plural societies throughout the world - Brooks Kelly, Brighid (Trinity College (Dublin, Ireland). Department of Political Science, 2007)
This project includes the most carefully constructed, large scale statistical analysis of the influence of the components of consociational government on stability. The variables and cases used in this analysis conform as closely as possible to the concepts of consociationalism, stability, and plural societies, as they are described by Lijphart in his extensive body of work regarding consociationalism. Accurate quantitative representation of his theory and recognition of the value of its analysis are facilitated by the discussions presented in Chapters 2 and 3. These chapters confirm the precise components of the theory, discuss criticisms that have been made concerning it, and describe another quantitative treatment of the performance of one of consociationalism’s components. This project’s quantitative analysis comprises multiple regression tests involving two sets of cases, which correspond to plural societies and plural societies which are also democratic. The latter set of cases and an independent controlling variable corresponding to democracy are used to ascertain whether consociationalism produces the stability which characterizes democracies, in contrast to the lack of upheaval, rebellion, and protest that results from severe oppression under undemocratic regimes. After the definition of plural societies to be used to choose cases is identified in Chapter 4, the independent variables and data representing them are identified and justified in Chapter 5.
Keywords: Political Science, Ph.D.; Ph.D. Trinity College Dublin